2000
DOI: 10.2355/isijinternational.40.902
|View full text |Cite
|
Sign up to set email alerts
|

Retained Austenite Characteristics and Tensile Properties in a TRIP Type Bainitic Sheet Steel.

Abstract: Retained austenite characteristics and tensile properties in a 0.2C-1.5Si-1.5Mn, mass%, high-strength cold-rolled "TRIP type bainitic steel" which was associated with the transformation induced plasticity (TRIP) of the retained austenite were investigated. The steel mainly consisted of bainitic ferrite lath matrix, blocky martensites and stable retained austenite films of 5-12 vol%. When austempered at temperatures above M S temperature, the steel possessed high tensile strength of 900 MPa, large total elongat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
129
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 233 publications
(137 citation statements)
references
References 18 publications
6
129
0
2
Order By: Relevance
“…5. 36) The decrease in yield strength with increasing cooling rate, as observed in Fig. 6, can be related to the lower content of pearlite, the presence of low strength ferrite, and some austenite in agreement with results reported by other investigators.…”
Section: Mechanical Properties 421 Influence Of Reheating Temperatsupporting
confidence: 81%
“…5. 36) The decrease in yield strength with increasing cooling rate, as observed in Fig. 6, can be related to the lower content of pearlite, the presence of low strength ferrite, and some austenite in agreement with results reported by other investigators.…”
Section: Mechanical Properties 421 Influence Of Reheating Temperatsupporting
confidence: 81%
“…It is important that the steels A-E do not contain any cementite in the bainitic ferrite lath structure, differing from the conventional structural steels such as SCM steels, as previously reported. [1,4] Figure 6(a) shows the variations in an initial volume fraction and carbon concentration of retained austenite as a function of hardenability factor in steels A-E. It is found that the carbon concentration decreases with increasing hardenability.…”
Section: Methodsmentioning
confidence: 99%
“…Advanced C-Si-Mn high-strength transformation-induced plasticity (TRIP)-aided steel with bainitic ferrite structure matrix (TRIP-aided bainitic ferrite steel; TBF steel) [1][2][3][4] possesses a good combination of tensile strength and stretch-flangeability. So, commercial TBF steels with tensile strength of 980-1180 MPa are applied to some automotive members in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Microstructures are generally formed by a bainitic ferrite matrix with or without carbides, depending on the alloying elements and the isothermal holding time, and retained austenite, in the form of thin films or martensite-austenite (MA) islands. [7][8][9][10][11][12][13] The isothermally obtained phase product is generally called bainite. While the bainitic ferrite is free of carbides in upper bainite, lower bainitic ferrite can contain a fine dispersion of plate-like carbides, depending on the silicon content.…”
Section: Introductionmentioning
confidence: 99%